Victor - Polydorou, Doros (My University, 2026)
“Victor”, an interactive/immersive performance inspired by the book “Frankenstein or The Modern Prometheus” by Mary Shelley. The protagonist of the book Victor Frankenstein creates and animates a new creature through chemical materials and old/dismembered body parts that belong to people who are no longer alive. In the play “Victor”, the viewer had the opportunity to experience but also to execute the story. The participants enter Victor’s workspace and pass through various interactive stations that give life to the creature. The choices which are made along the journey, in uence the nal performance.